Evaluation of alfalfa cultivars and estimates of repeatability coefficient of forage traits - Ferreira, Reinaldo de Paula; Botrel, Milton de Andrade; Pereira, Antonio Vander; Cruz, Cosme Damião (Pesquisa Agropecuaria Brasileira, 1999)
The objective of this study was to evaluate the performance of 42 cultivars of alfalfa (Medicago sativa L.) and to estimate the repeatability coefficient for dry matter production, leaf and stem protein content and disease tolerance features during the dry (April to September) and rainy (October to March) seasons with six cuts. Dry matter yield and leaf protein content presented significant variation in both seasons, although stem protein content and tolerance to diseases were different only during the dry season. Cultivars Crioula and Cibola had the best performance in most features. In general, the repeatability coefficient showed a low magnitude estimate (below 0,40). Regarding dry matter production, the cultivars showed similar behavior in both seasons, with repeatability coefficient ranging from 0.3195 to 0.4270, genotypic determination around 65% and the possibility to predict the real value after seven to nine cuts.